Framing Migration in Southern European Media: Perceptions of Spanish, Italian, and Greek Specialized Journalists. (2nd January 2023) - Arcila-Calderón, Carlos; Blanco-Herrero, David; Matsiola, María; Oller-Alonso, Martín; Saridou, Theodora; Splendore, Sergio; Veglis, Andreas
ABSTRACT: Greece, Italy, and Spain are the Southern European borders and the main entrances for migrants and refugees to Europe, a movement that was particularly visible after the 2015 "refugee crisis of the Mediterranean." In this context, immigration is used as a political tool, and the object of major media coverage. However, previous studies have shown that this coverage tends to be partial and prejudiced. This study, conducted during the COVID-19 pandemic, uses the frame building theory to study the perceptions of journalists covering migration issues regarding ways to improve the representation of migrants in the media of these three countries. For that, in-depth interviews were conducted with 94 Greek, Italian, and Spanish journalists. The precarity of the profession, the focus on conflictive approaches, and discrimination based on national origin or religion are mentioned as the biggest challenges. Professionals covering this information demand more individualized and deeper coverage, giving the migrants' condition greater visibility, and giving voice to the migrants themselves, as they are the protagonists of the stories. Greater attention to journalistic ethics and the defense of vulnerable groups is considered essential to achieve this.